Multiple-bank lending: Diversification and free-riding in monitoring - Carletti, Elena; Cerasi, Vittoria; Daltung, Sonja (Journal of Financial Intermediation, 2007)
This paper analyzes banks' choice between lending to firms individually and sharing lending with other banks, when firms and banks are subject to moral hazard and monitoring is essential. Multiple-bank lending is optimal whenever the benefit of greater diversification in terms of higher monitoring dominates the costs of free-riding and duplication of efforts. The model predicts a greater use of multiple-bank lending when banks are small relative to investment projects, firms are less profitable, and poor financial integration, regulation and inefficient judicial systems increase monitoring costs. These results are consistent with empirical observations concerning small business lending and loan syndication.